Performance evaluation of the Qiagen BK virus ASR on the NeuMoDx system - Amorce Lima; Luciano Soares; Caroline Simmons; Laura Rowe; Dominic Uy; Deanna Becker; Suzane Silbert (Journal of Clinical Virology Plus)
Background: BK virus (BKV) is the main cause of polyomavirus‐associated nephropathy in kidney transplant patients and hemorrhagic cystitis in bone marrow recipients. BKV quantitation by PCR is crucial in diagnostic and therapeutic management of transplant patients infected with BKV. We evaluated the performance of the Qiagen BKV ASR for the quantification of BKV on the NeuMoDx™ 96 System and compared the results to our standard of care (SOC) test, the Diasorin BKV ASR on the Liaison® MDX. Methods: The analytical performance was assessed using commercially available BKV Panels that meet the 1st WHO International Standards for BKV nucleic acid amplification techniques. The clinical performance was evaluated using 204 residual plasma and urine samples previously identified with the SOC assay. Results: The assay exhibited a strong linear correlation (R² = 0.9985) with the reference panel and an excellent analytical accuracy (R² = 0.9976). The LoD was determined to be 50 IU/mL with remarkable precision within and between days (SDEV 0.00—0.57 and 0.05—0.31, respectively). Of the 204 samples, only 10 (4.9 %) were discordant (PPA = 92.37 %; NPA = 100 %). Although the Qiagen BKV ASR quantified BKV DNA at an average of 0.48 Log IU/mL lower than the SOC, it showed a strong concordance to the SOC results. Compared to the SOC, the Qiagen BKV ASR had a more automated workflow, with less hands-on time, leading to quicker turnaround time. Conclusion: The Qiagen BKV ASR is specific, sensitive, and accurate in quantifying BKV in plasma and urine specimens on the fully automated NeuMoDx™ 96 System.